What can conservation strategies learn from the ecosystem services approach? Insights from ecosystem assessments in two Spanish Protected Areas - Berry, P; García-Llorente, M; Harrison, P; Palomo, I; Gómez-Baggethun, E; Iniesta-Arandia, I; Montes, C; García del Amo, D; Martín-López, B (Resilience Alliance, 2015)
Biodiversity conservation strategies that overlook the interests of local people are prone to create conflicts. The ecosystem service approach holds potential for integrating the social dimension in and around protected areas, but its implementation in conservation policies is still in its infancy. This research assesses the extent to which ecosystem services are considered and have been implemented in conservation strategies in protected areas. The study was conducted in two Spanish protected areas, covering a wetland (Doñana Natural and National Parks) and a Mediterranean mountain (Sierra Nevada Natural and National Parks) ecosystem. Data were collected from deliberative workshops with managers and researchers, face-to-face questionnaires with users and a review of management plans. We found that, beyond intrinsic values of biodiversity, these areas provide multiple ecosystem services that deserve further attention to ensure their sustained delivery. Our research shows that environmental managers and ecosystem service users have different perceptions and priorities regarding ecosystem services management. Environmental managers in both protected areas perceived that human-nature relationships and ecosystem service arguments are already widely included in management plans, if often not explicitly. We found that different ecosystem service categories receive uneven attention in management plans. These contained measures to manage provisioning and cultural services whereas measures for managing regulating services were perceived to be largely absent. We conclude by summarizing insights on how the ecosystem service approach may enhance management plans within protected areas.